Public service performance in the distribution of cash assistance for female heads of poor households in Semarang City - Auliansyah, Rahadian (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Background: This paper discusses the performance of public services in the distribution of direct cash assistance/Bantuan Langsung Tunai (BLT) for female heads of poor households in Semarang City, focusing on the aspects of planning, implementation, and program impact. Methods: The research aims to analyze the effectiveness of the BLT program, evaluate solutions to challenges faced, and formulate recommendations for sustainable improvement. Findings: The research results show that thorough and responsive planning, transparent implementation, and innovative solutions can enhance public service performance. The BLT program has a positive impact on empowering female heads of households through economic strengthening and active participation. Semarang City has successfully created a model of successful public service, providing hope for a higher quality future for female heads of households. Conclusion: Recommendations include increasing digital literacy and evaluating gender-responsive policies to support inclusive and sustainable development. Novelty/Originality of this Study: The study uniquely highlights the specific challenges and successes in the distribution of BLT to female heads of poor households in Semarang City, emphasizing the importance of gender-responsive policies and the empowerment of women. Its originality lies in its detailed focus on planning, implementation, and impact analysis, providing a model for improving public service performance in similar urban settings.